ChemInform Abstract: Carboxylation of Terminal Alkynes with CO2 Catalyzed by Bis(amidate) Rare‐Earth Metal Amides. Issue 29 (July 2015) - Cheng, Hao; Zhao, Bei; Yao, Yingming; Lu, Chengrong
Abstract Three bis(amidate) rare‐earth metal amides are synthesized (containing lanthanum, neodymium and yttrium) which are found to be efficient catalysts for the direct carboxylation of terminal alkynes with CO2.